THE EFFECT OF ANTIFUNGAL ACTIVITY OF β-1,3-GLUCANASE Trichoderma reesei AGAINST ROOT FUNGI OF Ganoderma philippii - Sri Wahyuni Budiarti; S.M. Widyastuti (Pusbindiklat - LIPI, 2011)
Purifi ed three isoform β-1,3-glucanases of 90 kDa β-1,3-glucanase-I, 75 kDa β-1,3-glucanase-II, and 64 kDa β-1,3-glucanase-III derived from Trichoderma reesei isolate T13were tested in vitro for its antifungal activity to the root fungi of Ganoderma philippii. Antifungal activity was tested by bioassay using a modifi ed cup plate method and microscopic observation to determine the presence of abnormal mycelia growth of G. philippii. The result showed that antifungal activity of those three isoform β-1 ,3-glucanase (β-1,3-glucanase-I, β-1,3 glucanase-II, and β-1,3-glucanase-III) in vitro could not form growth inhibition against the mycelia of G. philippii. Microscopic observation revealed that the enzyme caused necrotic lesion, whereas the combination of β-1,3-glucanase and chitinase from T. harzianum (Sigma) caused lyzed hyphae of G. philippii.